Phage therapy to treat cystic fibrosis Burkholderia cepacia complex lung infections: perspectives and challenges - Canning, Jack S.; Laucirica, Daniel R.; Ling, Kak-Ming; Nicol, Mark P.; Stick, Stephen M.; Kicic, Anthony (Frontiers in Microbiology, 2024)
Burkholderia cepacia complex is a cause of serious lung infections in people with cystic fibrosis, exhibiting extremely high levels of antimicrobial resistance. These infections are difficult to treat and are associated with high morbidity and mortality. With a notable lack of new antibiotic classes currently in development, exploring alternative antimicrobial strategies for Burkholderia cepacia complex is crucial. One potential alternative seeing renewed interest is the use of bacteriophage (phage) therapy. This review summarises what is currently known about Burkholderia cepacia complex in cystic fibrosis, as well as challenges and insights for using phages to treat Burkholderia cepacia complex lung infections.